(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The problem of climate change has been associated with predatory dynamics established in colonial times. This is referred to as “climate colonialism” to describe both the historical origins of the different vulnerability to environmental disasters between the global North and South and to highlight the harmful appropriation dynamics underlying some environmental policy measures. The aim is to provide a different key to assist the jurist in examining the instruments adopted to curb climate change. The last part of the article will provide an example of the application of this lens in the context of FTAs and VPAs.